Effect of Some Fungicides on Development of Vesicular Arbuscular Mycorrhizae and Growth of Sesbania sesban - Kumar, Anil; Tewari, R.; Shukla, A. (Indian Journal of Agroforestry, 2020)
A study was conducted to evaluate effect of six commonly used fungicides viz., Bavistin, Blitox, Captaf, Dithane M-45, Kavach and phenyl mercury acetate on indigenous vesicular arbuscular mycorrhizal endophytes. Sesbania sesban was used as test plant. The results showed that Blitox and Kavach were detrimental to vesicular arbuscular mycorrhizal infection. Bavistin, Captaf and phenyl mercury acetate were found to be compatible to native mycorrhizal micro-flora. These could be of use in situations, which warrant simultaneous plant disease control through Â fungicides and inoculation of tree seedlings with above mentioned fungi. Certain fungicidal treatments stimulated the vesicular arbuscular mycorrhizal colonization viz., Bavistin at 10 ppm, Dithane M-45 and phenyl mercury acetate at 50 and 100 ppm.